Implementasi Kebijakan Penetapan Badan Layanan Umum Museum Nasional Pada Kementerian Pendidikan, Kebudayaan, Riset, Dan Teknologi - Islam, Dirgantara Kusuma Nur; Ruhana , Faria; Dione, Frans (UIR Press, 2024)
The purpose of this study was to identify and analyze 1) the Implementation of the Establishment Policy of the National Museum Public Service Agency at the Ministry of Education, Culture, Research, and Technology, 2) Supporting and Inhibiting Factors of the Implementation of the National Museum Public Service Agency Establishment Policy at the Ministry of Education, Culture, Research, and Technology, and 3) The efforts of the Ministry of Education, Culture, Research, and Technology in overcoming obstacles to the implementation process of the determination policy public service agency of the National Museum. The research method used a qualitative approach, data collection techniques were observation, interviews, and documentation. The results of this research were: 1) The implementation of the policy of establishing the Museum Public Service Agency has been implemented by conducting internal and external communication, optimizing the use of existing resources including employees, infrastructure facilities and adequate budgets, making work systems by compiling business processes, standard operational procedures and derivative rules or regulations governing the running of public servants such as setting visiting and utilization tariffs, business strategic plan and finally develop a simple and effective bureaucratic structure in order to create an agile organization, 2) Supporting factors: There is policy support from the ministry, regulatory support, employee support, asset support, and strategic geographical location. Inhibiting factors: there is still a lack of understanding of the team in preparing the proposed documents, policies, and fears of employees, as well as facilities that need to be improved, 3) Efforts of the Ministry of Education, Culture, Research, and Technology in overcoming obstacles such as: preparing follow-up documents on recommendations for improvement, socialization and internal and external coordination meetings, making service programs, drafting derivative regulations on policy implementation.